THE IMPLEMENTATION OF ALTERNATIVE ASSESSMENT FOR EFL STUDENT - Alfi Hidayatu Miqawati; Fachrurrazy Fachrurrazy (Progresif : Media Publikasi Ilmiah, 2021)
This study investigated the implementation of the alternative assessments for EFL student writing. To collect data for this study, information was obtained from an English teacher teaching at an A accredited Public Junior High School in Bondowoso. To make the process of data collection and analysis easier, some instruments were used, which were observation, interview, and documentation. The findings showed that there were some alternative assessments that the teacher applied. The alternative assessments applied were story telling, writing samples, portfolio, teacher observation, and conference. The portfolio assessment was no longer done since she found some difficulties and obstacles in applying it. There were two considerations of choosing certain language assessments. The first consideration was the language skills that were going to be assessed. The second consideration was the applicability of an alternative assessment. The applied alternative assessments gave positive effect to the students compared to the traditional ones, in term of gaining the students’ mastery and participation.